Time course of NT‐proBNP levels after acute ischemic stroke. (7th March 2013) - Fonseca, A. C.; Matias, J. S.; e Melo, T. P.; Pires, C.; Geraldes, R.; Canhão, P.; Brito, D.; Ferro, J. M.
Abstract : Background: Studies suggest that N‐terminal‐pro‐brain natriuretic peptide (NT‐proBNP) can be a biomarker of cardioembolic stroke. However, the best time to measure it after stroke is unknown. We studied the time course of NT‐proBNP in patients with ischemic stroke. Methods: Consecutive acute ischemic stroke patients were admitted over 10 months to a Stroke Unit. Stroke type was classified according to TOAST. Blood samples were drawn within 24, 48, and 72 hours after stroke. Friedman test was used to compare NT‐proBNP values across the 3 times in all, cardioembolic and non‐cardioembolic stroke patients. Post hoc analysis with Wilcoxon signed‐rank tests was conducted with a Bonferroni correction. Mann–Whitney test was used to compare median values of NT‐proBNP between cardioembolic and non‐cardioembolic stroke patients. ROC curves were drawn to determine NT‐proBNP accuracy to diagnose cardioembolic stroke at 24, 48, and 72 hours after stroke onset. Results: One hundred and one patients were included (29 cardioembolic) with a mean age of 64.5±12.3 years. NT‐proBNP values for cardioembolic stroke were significantly higher ( P  < 0.001) than for non‐cardioembolic stroke in the 3 time points. NT‐proBNP was highest in the first 24–48 h after ischemic stroke and decreased significantly 72 h after stroke onset. The area under the curve for the three time points was similar. Conclusion: NT‐proBNP levels were highest in the first 2 days after ischemic stroke and declined significantly thereafter. However, the area under the curve for the three time points was similar. The first 72 hours after ischemic stroke have a similar diagnostic accuracy to diagnose cardioembolic stroke.